Pengaruh Konsentrasi Pupuk Organik Cair Super Bionik dan Varietas Kacang Tanah terhadap Pertumbuhan dan Hasil - Zuyasna Zuyasna; Halimursyadah Halimursyadah; Chandra Saputra (Jurnal Agrista, 2010)
Effect of Organic Liquid Fertilizer and Peanut Variety on the Growth and YieldABSTRACT. The objective of this study were to investigate several varieties and liquid organic fertilizer on the growth at the yield of peanut of the tsunami affected area and also to identify the interaction between the two factors. The research was conducted at the Lamnyong river flood plain which is located at west sector of Komplek Pelajar Mahasiswa (KOPELMA) Darussalam – Banda Aceh from March to Mei 2009. Randomized completely block design with two factor was used on this experiment using three replications. The first factor was peanut variety (i.e. Singa, Kuala Batee and Tangse), and the second factors was Super Bionik fertilizer concentrations (i.e. 0 cc; 0.9 cc; 1,8 cc /225cc). The variety significantly influenced the plants height on 45 days after planting, the amount of ginofore, the plant wet weight, and 100 seed weight, however the variety not significantly influenced other parameters (i.e. the amount of the branches at 45 days after planting, the total pods, and the amount of full pod). The result showed that Super Bionic concentrations not significantly influenced all parameters observed, and no interactions between the variety and the fertilizer concentration occurred on the parameters observed.